About Universals and God: A Voice in the Discussion - Rosiak, Marek (Roczniki Filozoficzne, 2024)
Issues analyzed in this paper are reconsideration of problems discussed in Stanislaus Judycki’s study “Bóg i uniwersalia” (God and Universals). Certain arguments for and against universal being are discussed and some interpretations of classical standpoints in the so called controversy over universals are proposed. A possible connection of the problems concerning universals and God’s existence are also discussed.